On Efficient Distribution of Data in Multicast Networks: QoS in Scalable Networks - Lowu, Francis; Baryamureeba, Venansius (Springer, 2005)
Multimedia applications or real-time applications such as audio and video on demand, teleconferencing and whiteboard sharing require Quality of Service (QoS) guarantee assurance. QoS constraints, namely required bandwidth, end-to-end delay and delay jitter are the major parameters that need to be satisfied in order to have quality assurance in a dynamic multicast network. In this paper we investigate the effect of the QoS constraints on multicast network applications and services during the processes of routing. Lastly, we propose linear routing tree algorithms for required bandwidth, end-to-end delay and delay jitter.
Keywords: Data; Multicast Networks; QoS; Scalable Networks